Battery Chargers in Electric Vehicles - Kaptan, Deniz; Cansever, Galip (IEEE, 2018)
Batterychargers are the energy transmission part of electric vehicles between the grid (or electric energy source) and the vehicle. This energy transmission process has a great effect on the technology of electric vehicles. Charging a vehicle as fast as possible is necessary for an electric vehicle to compete with the internal combustion engine vehicles. The technology has been dealing with this process near past, while charging a car was taking a few hours, this time is reducing day after day. In this paper it is aimed to give some information about the current technologies of chargers(only the chargers with cable not wireless chargers) and it is also aimed to design a trial Simulink model for chargers. When the literature is considered, simulation samples of chargers are little so increasing these samples is important to improve the technology offast charging.
Keywords: electric vehicles (EVs); battery chargers; state of charge (SOC); phase locked loop (PLL); Automation & Control Systems; Computer Science; Engineering